The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1021/bi9820659
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Potent Natural Product Inhibitor Balanol in Complex with the Catalytic Subunit of cAMP-Dependent Protein Kinase

Abstract: Endogenous protein kinase inhibitors are essential for a wide range of physiological functions. These endogenous inhibitors may mimic peptide substrates as in the case of the heat-stable protein kinase inhibitor (PKI), or they may mimic nucleotide triphosphates. Natural product inhibitors, endogenous to the unique organisms producing them, can be potent exogenous inhibitors against foreign protein kinases. Balanol is a natural product inhibitor exhibiting low nanomolar K i values against serine and threonine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
103
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(112 citation statements)
references
References 109 publications
8
103
0
1
Order By: Relevance
“…6). The finding that active site inhibitors lock the phosphorylation sites on the C-terminal tail in a phosphatase-resistant conformation is consistent with structural studies of PKA that showed that the C-terminal tail is highly ordered when inhibitor is bound and highly disordered in the apo structure (39,40). It is interesting to note that occupancy of the active site by ATP analogues such as Bis I expels the autoinhibitory pseudosubstrate from the substrate-binding cavity (32), an event that, in itself, increases the phosphatase sensitivity of PKC by 2 orders of magnitude (7).…”
Section: Discussionsupporting
confidence: 84%
“…6). The finding that active site inhibitors lock the phosphorylation sites on the C-terminal tail in a phosphatase-resistant conformation is consistent with structural studies of PKA that showed that the C-terminal tail is highly ordered when inhibitor is bound and highly disordered in the apo structure (39,40). It is interesting to note that occupancy of the active site by ATP analogues such as Bis I expels the autoinhibitory pseudosubstrate from the substrate-binding cavity (32), an event that, in itself, increases the phosphatase sensitivity of PKC by 2 orders of magnitude (7).…”
Section: Discussionsupporting
confidence: 84%
“…The A-ring occupies the adenine ring subsite, the B-ring occupies the ribose subsite, and the C-and D-rings mimic the triphosphates, but occupy a distinct space. These spaces are the A-ring subsite, B-ring subsite, and C-and D-ring subsite (11). ATP (black stick) was taken from the C:ATP:IP20 structure (PDB code 1ATP) (2) and balanol (shown as a ball-andstick model) from the C:Bal structure (PDB code 1BX6) (11).…”
mentioning
confidence: 99%
“…These spaces are the A-ring subsite, B-ring subsite, and C-and D-ring subsite (11). ATP (black stick) was taken from the C:ATP:IP20 structure (PDB code 1ATP) (2) and balanol (shown as a ball-andstick model) from the C:Bal structure (PDB code 1BX6) (11). Atoms are colored by type: oxygen (red), nitrogen (blue), and carbon (black).…”
mentioning
confidence: 99%
“…The structure of PKA from the X-ray crystal complex structure (pdb code: 1bx6) (ref. 19) of PKA and bananol, which is an inhibitor of PKA, was used for docking OSU03013. To add hydrogen atoms, the all-atom molecular modeling program, Amber, was used first.…”
Section: Methodsmentioning
confidence: 99%
“…Atom charges on phosphoserine SEP338 and phosphothreonine TPO197 were obtained from Amber as well. For docking calculation, a docking space of 22.5 Â 22.5 Â 22.5 Å 3 centered around the ligand binding site (19) was used to ensure sufficient space exploration for ligand docking. Most other docking parameters were set to Autodock default parameters.…”
Section: Methodsmentioning
confidence: 99%